2013
DOI: 10.1055/s-0033-1345176
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Modulates the Expression of Molecules Linked to Insulin Action and Glucose Uptake in Endometrial Cells

Abstract: Polycystic ovary syndrome (PCOS) is a common hyperandrogenic disorder associated with insulin resistance. Insulin exerts its metabolic function by activating the PI3K/Akt pathway and favoring glucose uptake. Caveolin-1 is a scaffolding protein which increases insulin receptor (IR) stability. Alternatively, activation of IR increases caveolin-1 phosphorylation on tyrosine-14. Furthermore, endometrial tissue from PCOS patients is proposed to be insulin resistant; however, the particular role of testosterone in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Decreased insulin-stimulated glucose transport in skeletal muscle has been shown to be a major contributing factor to IR in patients with T2D and obesity. Additionally, it has been reported that T reduced insulin-stimulated glucose uptake in cultured female adipocytes [ 21 ] and endometrial cells [ 34 ]. In the present work, we demonstrated that T decreased insulin-stimulated GLUT4 translocation and glucose uptake in C2C12 myotubes, which promoted insulin resistance in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased insulin-stimulated glucose transport in skeletal muscle has been shown to be a major contributing factor to IR in patients with T2D and obesity. Additionally, it has been reported that T reduced insulin-stimulated glucose uptake in cultured female adipocytes [ 21 ] and endometrial cells [ 34 ]. In the present work, we demonstrated that T decreased insulin-stimulated GLUT4 translocation and glucose uptake in C2C12 myotubes, which promoted insulin resistance in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in endometrial function may also be a significant cause of low fertility in PCOS patients. Insulin resistance, as a characteristic metabolic feature in PCOS, affects the physiological function in uterine endometrium relating to endometrial receptivity(ER) [35,36]. The ER of patients with PCOS is worse than that of normal women [37].…”
Section: Ir and The Endometrial Receptivity In Pcosmentioning
confidence: 99%
“…Several diseases have been reported to both impair decidualization and predispose to preeclampsia including polycystic ovarian syndrome [7984], obesity [79, 80, 85, 86], diabetes mellitus [8789], and endometriosis [9092]. These comorbidities may exert their disruptive action on the endometrium through anomalous inflammation, exaggerated production of androgens, insulin, and homocysteine, as well as pathological epigenetic modifications [79, 91, 9396]. Indeed, epigenetic dysregulation is another likely instigating factor, insofar as much of the normal biological process of decidualization is epigenetically regulated [97103].…”
Section: Potential Mechanisms Of Impaired Decidualization In Preeclammentioning
confidence: 99%